STANDARISASI TATABAHASA BAHASA SASAK (Sebuah Pertimbangan dari Aspek Linguistik) - Ahmad Sirulhaq (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
This paper aims at presenting Sasak language structure in relation to the efforts of standardization toward Sasak language dialect. This presentation stems at the universal principles of linguistic structure which are clear, succinct, and simple to be managed as what have been stated by Poedjosoedarmo. Based on those principles, this study shows that among the four dialects in Sasak language, a-dialect in fact owns an opportunity to be treated as a reference to formulate a standardized dialect linguistic system.